2015
DOI: 10.1016/j.tsf.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ZnSnP2 thin films by phosphidation

Abstract: a b s t r a c tZnSnP 2 is a promising candidate as a solar absorbing material consisting of earth-abundant and low-toxic elements. In this study, the phosphidation method, where co-sputtered Zn-Sn thin films react with phosphorus gas, was adopted for fabricating ZnSnP 2 thin films. To establish the conditions for producing ZnSnP 2 thin films, we investigated the influence of phosphidation temperature on the product phases, and interpreted the experimental results using chemical potential diagrams of the Zn-Sn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
2
14
0
Order By: Relevance
“…In our previous work on ZnSnP 2 , some protrusions with lengths of a few micrometers were formed on ZnSnP 2 thin films by the so-called VLS (vapor−liquid−solid) growth mode. 28,33 In the present study, such protrusions were not observed in CdSnP 2 thin films fabricated by a similar phosphidation process. It is interesting that CdSnP 2 and ZnSnP 2 showed different morphologies in spite of the similarity in constituent elements and crystal structures.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…In our previous work on ZnSnP 2 , some protrusions with lengths of a few micrometers were formed on ZnSnP 2 thin films by the so-called VLS (vapor−liquid−solid) growth mode. 28,33 In the present study, such protrusions were not observed in CdSnP 2 thin films fabricated by a similar phosphidation process. It is interesting that CdSnP 2 and ZnSnP 2 showed different morphologies in spite of the similarity in constituent elements and crystal structures.…”
Section: Resultssupporting
confidence: 48%
“…The details of the experimental conditions were described in our previous 6 work. 28 We used two phase sample with Sn and Sn4P3 as a phosphorus source and 7 phosphorus gas was transported to the precursor thin films using Ar carrier gas, which 8 was deoxidized by passing through a Ti sponge heated at 900 C. The partial pressure of 9 phosphorus was set at approximately 10 −2 atm by controlling the temperature of two phase 10 sample.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been explored for the preparation of ZTP in form of crystals and thin films using elemental Zn, Sn and P or in combination of Zn-P and Sn-P compounds as starting materials. They include melt solution growth [4,[13][14][15], flux method [9,10], thermal or electron-beam evaporation [2,11,12,16,17], molecular beam epitaxy [5], liquid phase epitaxy [18], phosphidation of Zn-Sn layers [8,19] and others [20], generally, involving high temperature ([ 600°C) and/or vacuum. In some of these methods, the processes are very tricky due to the complexity in thermodynamic phase formation and a large difference in the vapor pressure between Zn and Sn [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In addition, a high absorption coefficient of about 10 5 cm À1 in the visible light region has been reported. 11,12 Although ZnSnP 2 thin films have been fabricated using several methods such as co-evaporation, 11,13,14 chemical vapor deposition, 15 liquid phase epitaxy, 16,17 molecular beam epitaxy, [18][19][20] and phosphidation, 21 solar cells based on ZnSnP 2 have not been investigated.…”
Section: Introductionmentioning
confidence: 99%